The Phenomenon of E-Dakwah in the New Normal Era: Digital Literacy of Virtual Da'i in Da'wah Activities - Rila Setyaningsih (International Journal of Islamic Thought and Humanities, 2023)
The emergence of the new normal era brought many changes in various aspects of life, including da'wah activities. Adaptation of the implementation of da'wah online or called e-da'wah is an innovation that can be done so that da'wah activities can continue to run. The phenomenon of e-da'wah in the new normal era is an important and interesting research to study. This study aims to analyze the digital literacy experience of virtual preachers in carrying out da'wah activities online in the new normal era. The research method used is qualitative with a phenomenological approach to explore the experience of digital literacy preachers, especially those related to communication and collaboration elements. Data analysis was carried out by reducing steps, presenting data and drawing conclusions. The results showed that the ability of the virtual da'i in Jintap Ponorogo Village in carrying out da'wah in the new normal era was at the basic level for use skills and communicative abilities, while critical understanding was at the medium level. This research is expected to contribute to optimizing the implementation of e-da'wah in the new normal era, especially by increasing digital literacy for virtual preachers in Jintap Village, Ponorogo.